2011
DOI: 10.1614/ws-d-10-00169.1
|View full text |Cite
|
Sign up to set email alerts
|

Galegine Content in Goatsrue (Galega officinalis) Varies by Plant Part and Phenological Growth Stage

Abstract: Goatsrue is a member of the Fabaceae family, native to Europe and western Asia. It contains the toxic alkaloid galegine. The objective of the study was to describe galegine concentration in aboveground goatsrue plant parts and total galegine pools over phenological growth stages. Twenty goatsrue plants at four locations were selected and a stalk was harvested from each at five stages of phenological development and separated into parts. Plant parts were freeze-dried, ground, and analyzed with liquid chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Because both costs and benefits are liable to change with plant age and stage, the level of expression of plant defences is predicted to be age dependent-a prediction that is now supported by a growing number of empirical studies investigating a wide range of plant species and defence types (e.g., Boege et al 2007;Elger et al 2009;Oldham et al 2011;Broekgaarden et al 2012). Of the four main categories of resistance types-constitutive-direct resistance, constitutive- 2 for log(x ?…”
Section: Discussionmentioning
confidence: 99%
“…Because both costs and benefits are liable to change with plant age and stage, the level of expression of plant defences is predicted to be age dependent-a prediction that is now supported by a growing number of empirical studies investigating a wide range of plant species and defence types (e.g., Boege et al 2007;Elger et al 2009;Oldham et al 2011;Broekgaarden et al 2012). Of the four main categories of resistance types-constitutive-direct resistance, constitutive- 2 for log(x ?…”
Section: Discussionmentioning
confidence: 99%
“…The mean sum of guanidines in the analyzed samples was calculated as 8.08 mg/g DW. A study of Oldham et al [ 24 ] indicated that the galegine content varied over the plant tissues and growth stages. The highest level of this compound was observed for reproductive tissues (6.32–8.53 mg/g, on average 7.35 mg/g DW), followed by leaves (2.8–6.22 mg/g, on average 4.25 mg/g DW) and the stem (1.27–1.85 mg/g, on average 1.44 mg/g DW).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, many recent studies have reported that other groups of phytochemicals commonly occurring in plants-e.g., flavonoids and phenolic acids-also scavenge RCS and free radicals such as reactive oxygen species (ROS), which both demonstrate a prominent role in the pathogenesis of endothelial dysfunction related to diabetes mellitus [22,23] However, although the therapeutic properties of goat's rue have long been recognized and appreciated in traditional medicine, the study of the phytochemical profile of the G. officinalis herb has been barely addressed. Previous studies on the composition of this species were focused on seed phytochemistry, mainly concerning amino compounds [24]. The chemical constitution of its polyphenolic fraction has received much less attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation